Presentación del dossier - Rivera Rivera, Ronald (2022)
As part of the efforts of the Sede de Occidente to reflect critically on the teaching of the arts and languages, this introduction explains the motivations that gave rise to the organization of the “Primer Congreso Centroamericano sobre Didáctica de la Lengua y Literatura”, held in mid-November of the previous year. It also constitutes a preamble to the pertinent articles presented by various participants in this activity, which, from different theoretical perspectives, invite readers to find new ways to improve the educational process.